Responding to different text genres for increased ESL listening skills and adult literacy development - Adversario, Jan; Larrotta, Clarena (American Journal of Education and Learning, 2025)
Listening is an essential component of English language acquisition and extremely important to communicate with others. This article highlights the importance for instructors and learners to understand factors that make listening difficult. This qualitative study describes findings from teaching English as a second language to 20 adult learners enrolled in an intermediate class at a community college. It discusses the teaching of listening as a process following a three-step cycle that includes pre-listening, listening, and post-listening activities while also using a variety of text genres such as news reports, poems and songs, commercials and advertisement, children’s literature, and financial literature. Data included classroom field notes, steps teaching listening as a process, and a qualitative questionnaire. Findings are presented by outlining the process of teaching listening as well as the literacy connection resulting from implementing this approach. Defining the text genre, as well as describing the features and language functions involved in listening, made the listening practice more meaningful for English learners. Based on the questionnaire responses, explicitly teaching listening as a process and exposure to different text genres positively impacted the students’ learning. This teaching approach encouraged deeper engagement with the message making the connection between listening practice and English literacy development readily evident. Exposure to listening to a variety of text genres enriched the learners’ ability to use language meaningfully and contextually. It develops listening comprehension by allowing the learner to gain understanding of language in the broader context of the human experience.